Cloning and sequence analysis of a chymotrypsinlike protease from Treponema denticola. - Arakawa, S (1994)
A clone expressing a Treponema denticola chymotrypsinlike protease from recombinant plasmid pSA2 was identified in a genomic library of T. denticola ATCC 35405. Nucleotide sequencing of the insert identified an open reading frame, designated the prtB gene, which codes for the protease. Two potential inverted repeat sequences are present both upstream and downstream from the prtB gene. The prtB gene would code for a putative protein of 273 amino acids with a calculated molecular mass of 30.4 kDa and an estimated pI of 7.0. The G+C content of the gene is 40.3%. The results of maxicell analysis are consistent with the expression of a 30-kDa protease from the prtB gene. Preliminary characterization of the protease indicated that it was inhibited by the protease inhibitors phenylmethylsulfonyl fluoride, diisopropylfluorophosphate, and N-tosyl-L-phenylalanine chloromethyl ketone but not by N alpha-p-tosyl-L-lysine chloromethyl ketone. Purification of the protease was accomplished with the PinPoint protein purification system following construction of site-directed mutagenized plasmid pXa-3:2. The purified protease degraded human and bovine serum albumins as well as casein. Furthermore, hemolysis of sheep erythrocytes by the protease was observed. Northern (RNA) blot analysis of mRNA extracted from strain 35405 indicated a single 1.9-kb mRNA species containing the prtB transcript. In addition, the results of primer extension analysis indicated that transcription was initiated primarily at a T residue. However, no corresponding -10 and -35 sequences related to Escherichia coli promoter sequences were identified. The availability of the purified protein and its gene will aid in evaluating the potential role of the protease in the physiology and virulence of T. denticola since proteases may play a key role in oral treponemal pathogenicity.